A Monetary and Fiscal History of the United States, 1961–2021 - Leeper, Eric M. (Journal of Economic Literature, 2023)
Eric M. Leeper of Department of Economics, University of Virginia reviews “A Monetary and Fiscal History of the United States, 1961-2021” by Alan S. Blinder. The Econlit abstract of this book begins: “Examines monetary and fiscal policy in the United States since the 1960s, chronicling how stabilization policy struggled to fight recessions, unemployment, and inflation.”